High- vs. low-spin Ni2+ in elongated octahedral environments: Sr2NiO2Cu2Se2, Sr2NiO2Cu2S2 and Sr2NiO2Cu2(Se1-xSx)2 - Smyth, RD; Blandy, JN; Yu, Z; Liu, S; Topping, CV; Cassidy, SJ; Smura, CF; Woodruff, DN; Manuel, P; Bull, CL; Funnell, NP; Ridley, CJ; et al. (American Chemical Society, 2022)
Sr2NiO2Cu2Se2, comprising alternating [Sr2NiO2]2+ and [Cu2Se2]2– layers, is reported. Powder neutron diffraction shows that the Ni2+ ions, which are in a highly elongated NiO4Se2 environment with D4h symmetry, adopt a high-spin configuration and carry localized magnetic moments which order antiferromagnetically below ∼160 K in a √2a × √2a × 2c expansion of the nuclear cell with an ordered moment of 1.31(2) μB per Ni2+ ion. The adoption of the high-spin configuration for this d8 cation in a pseudo-square-planar ligand field is supported by consideration of the experimental bond lengths and the results of density functional theory (DFT) calculations. This is in contrast to the sulfide analogue Sr2NiO2Cu2S2, which, according to both experiment and DFT calculations, has a much more elongated ligand field, more consistent with the low-spin configuration commonly found for square-planar Ni2+, and accordingly, there is no evidence for magnetic moment on the Ni2+ ions. Examination of the solid solution Sr2NiO2Cu2(Se1–xSx)2 shows direct evidence from the evolution of the crystal structure and the magnetic ordering for the transition from high-spin selenide-rich compounds to low-spin sulfide-rich compounds as a function of composition. Compression of Sr2NiO2Cu2Se2 up to 7.2 GPa does not show any structural signature of a change in the spin state. Consideration of the experimental and computed Ni2+ coordination environments and their subtle changes as a function of temperature, in addition to transitions evident in the transport properties and magnetic susceptibilities in the end members, Sr2NiO2Cu2Se2 and Sr2NiO2Cu2S2, suggest that simple high-spin and low-spin models for Ni2+ may not be entirely appropriate and point to further complexities in these compounds.